Effects of Garlic (Allium sativum) Extract on the Growth and Survival of Nile Tilapia (Oreochromis niloticus) Fingerlings at High Stocking Density - Anggriani, Dinda Shafira; Afriani, Dwi Tika; Syafitri, Emmy (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effect of garlic extract supplementation as an immunostimulant and feed additive on the survival of Nile tilapia fry reared in an intensive aquaculture system under high stocking density, and to determine the most effective dosage. The study employed an experimental method using a Completely Randomized Design (CRD) consisting of four treatments with three replicates: no extract, 5 g/kg, 10 g/kg, and 15 g/kg of feed administered over a 28-day rearing period. The primary parameter observed was survival rate, supported by growth data. Data were analyzed using ANOVA at a 95% confidence level, followed by the Least Significant Difference (LSD) test. The results showed that garlic extract supplementation improved survival compared with the control, with values of 53.3%, 61.7%, 70.0%, and 65.0%, respectively. The treatment with 10 g/kg feed produced the highest and most optimal survival rate. A higher dose did not result in further improvement, presumably because of reduced feed palatability and the physiological response of the fish. It can be concluded that garlic extract supplementation significantly affected the performance of Nile tilapia fry, with 10 g/kg identified as the most effective dose for enhancing resistance to environmental stress. This study also provides a practical contribution by recommending an optimal dose of natural feed additive for intensive aquaculture systems.